Nuclear Power Plant and Uzbekistan: how will a nuclear power plant contribute to the integration of the Republic of Uzbekistan into the global community - Akhrorova Sarvinabonu Askarovna; Muminov Asilbek Nodirovich (Genius Journals, 2022)
This article examines the economic, environmental, political prospects for the creation of a nuclear power plant in Uzbekistan in the face of a lack of electric energy. The situation in Uzbekistan and the state's need for energy are described in detail, options for solving this problem are listed. It explains why the right decision for Uzbekistan is to build a nuclear power plant, taking into account climatic conditions and the amount of uranium produced. This is an important step forward in the development of science, education, economics and medicine, since it entails the need for qualified personnel, the latest technologies and the production of radioactive materials on an industrial scale. The safety advantages of nuclear power plants are mentioned, compared to other energy sources such as thermal and hydroelectric power plants. The article shows the need to increase sustainable methods of energy production, profitable both economically and ecologically in long term
Keywords: Uranium; Renewable energy source; Integration; Electricity